Biofilm potentialities in water quality rehabilitation in urban streams - Oliveira, Flavia Franco de (2019)
Environmentally sustainable technologies have become interesting options in the rehabilitation of eutrophic aquatic ecosystems. One of the bioremediation methodologies that can be used is the biofilm habitat expansion, using submerged artificial substrates, with the purpose of promoting the growth and biomass increase of this community, thus increasing the self-purification capacity of aquatic ecosystems. According to several authors, the use of biofilm has several advantages over other technologies because: (a) it consists of several types of organisms (microalgae, fungi, bacteria, protozoa and also small animals); that is, as it is a complete community, processes of production, consumption and decomposition occur, making the treatment more effective; (b) can be found anywhere in the watercourse; (c) plays an important role in the nutrient recycling and transfer process; (d) is attached to a given substrate, and (f) is easily incorporated into bioreactors. In the present work polyethylene “curtains” were used as substrate for biofilm in two eutrophic streams, located in two different climatic regions: tropical region (Rio Cabelo, João Pessoa, Brazil) and Mediterranean region (Rio Fervença, Bragança, Portugal). The spatial and temporal dimension was different in both experiments. Preliminary results showed a tendency to reduce nutrient concentrations and increase dissolved oxygen concentrations in the studied streams after the application of biofilm substrates, indicating that there is a tendency to improve water quality and therefore, an interesting potential of this technology.